New Technology For Longwall Ground Control - Proceedings: U.S. Bureau Of Mines Technology Transfer Seminar - Christopher Mark (The National Institute for Occupational Safety and Health (NIOSH), 1994)
This proceedings volume contains papers presented at W U.S. Bureau of Mines (USBM) technology transfer seminars on New Technology for Longwall Ground Control. These seminars were conducted in Washington, PA, on April 12, 1994, and Denver, CO, on May 10, 1994. The papers herein describe several new, highly practical USBM technologies now available for ground control in longwall mines, including lie Coal Mice Roof Rating (CMRR), cable bolts, the MULSIM/NL model, and the Wood Crib Performance Model. Other significant topics addressed include longwall panel layout, coal pillar design, horizontal stress in longwall mines, roof support selection for gate entries, and ground control monitoring.